Establishing and evaluating phrasal verb use in a Malaysian ESL secondary school textbook corpus - Zarifi, Abdolvahed (2013)
Phrasal verbs are one of the most notoriously puzzling aspects of English language instruction. Despite their potential complexities and idiosyncrasies, they are of high relevance for ESL/EFL learners because knowledge of them is often equated with language proficiency and fluency. With more and more phrasal verbs appearing in textbooks, it is worth considering whether the use of these structures is informed by research findings. This is of main research concern as ESL textbooks are reported to be far from in keeping with natural facts and they often misrepresent language phenomena. The present corpus-based content analysis study, thus, seeks to 1) identify all the instances of phrasal verbs and determine their frequency and distribution, 2) provide a typology of the syntactic structures of these combinations,3) explore the treatment of the combinations in terms of their potential word meanings, and 4) investigate the pedagogical exploitation of these combinations in the Malaysian ESL Forms One through Five prescribed for students in the secondary school level. To achieve this importance, use was made of the Zar-Test,Focus Framework, Cognitive Load Framework, all developed by the researcher,along with WordSmith version 4.0 and the Oxford Dictionary of Phrasal Verbs as the research instruments. Findings revealed that the selection, presentation and sequencing of these combinations were based more on authors’ intuition than on empirical findings and pedagogical principles. To begin with, some combinations of frequent use in natural language were not at all so in the ESL corpus and vice versa. Despite the large number of phrasal verbs in the corpus, their presentation was far from satisfactory,with some being over-repeated at the expense of some others. Secondly, the grammatical patterns of phrasal verbs were distributed unevenly across the corpus both in terms of type and number. Thirdly, these combinations were inadequately presented in semantic terms. While a few combinations were used with all their different potential dictionary meanings, many others were narrowly used with only few possible meanings, hence not fleshed out appropriately. Findings also cast light on some of the traces of the localized variety of English in the use of phrasal verbs in the corpus. Finally, these combinations turned out not to be appropriately pedagogically used. Only 6% of the combinations in the reading texts received direct focus, with the overwhelming majority being either in Indirect Focus or in No Focus status. The learning activities on phrasal verbs were, likewise, shown to have moderate cognitive loads, hence not fully appropriate for deep learning of these units. In addition to the research findings, this study has a few methodological innovations to contribute. Although literature offers a number of tests for the identification of phrasal verbs, these tests are rather complicated, including 7 to 9 items. They are subject to exceptions and counterexamples as well. Moreover, they tend to differentiate Verb + Real Particles from Verb + Prepositions but remain silent on how they are distinct from Verb + Adverb particles. The Zar-Test of Initialization, on the other hand, consists of only one single item that can be applied in three stages to identify the different types of these combinations. Moreover, the study offers two separate frameworks, namely Cognitive Load Framework and Focus Framework, for the evaluation of the use of phrasal verbs in ELT textbooks. Unlike Laufer and Hulsijn’s Involvement Load Hypothesis which is learner-based, the Cognitive Load Framework is mainly task-based and purely cognitively oriented. The framework has been validated as a helpful tool in determining the cognitive load of the various learning activities dealing with not only the phrasal verbs but also other lexical elements. In a similar way, the Focus Framework provides a sound basis for the assessment of different lexical items appearing in the reading texts of the instructional materials.